Physico-chemical attributes of humic acid extracted from tropical pect - Mohd Hanif, Ahmad Husni; Sani Babu, Shanti Devi; Manas, Abdul Rahman; Balasundram, Siva Kumar (Universiti Putra Malaysia Press, 1996)
Basic research conducted on humic acid (HA) in tropical soils is limited. A study was conducted to characterize HA extracted from tropical peat by elemental and functional group analyses, infrared (IR) spectra and by direct examination on HA using scanning electron microscopy (SEM). From the elemental analysis it was found that C ranged from 40.26 - 53.26%, H 4.84 - 6.36%,038.39 - 51.62%, N 1.51- 2.64%, and P 0.02 - 0.06%. Studies of functional groups indicated that the carboxyl group present in HA of tropical peat was about twice as high as that of phenolic hydroxyl groups. From IR spectra, the HA had an aromatic character. Results of IR analysis also exhibited consistently similar spectra, demonstrating that regardless of place of origin, the extracted humic compound had a similar structure and was composed of the same functional groups. Electron microscopic examination of dried HA showed a sub-angular blocky shape which varied in size. All extracted HA exhibited similar form.